2016
DOI: 10.3390/w8120592
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Modeling in Support of Water Resources Management and Planning under Complex Climate, Regulatory, and Economic Stresses

Abstract: Abstract:Groundwater is an important resource that meets part or all of the water demand in many developed basins. Since it is an integral part of the hydrologic cycle, management of groundwater resources must consider not only the management of surface flows but also the variability in climate. In addition, agricultural and urban activities both affect the availability of water resources and are affected by it. Arguably, the Central Valley of the State of California, USA, can be considered a basin where all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In a prior study of the watershed (MWH, ), several “level of development” scenarios using the California Central Valley Groundwater‐Surface Water Simulation Model (Brush, Dogrul, & Kadir, ) were created to simulate a suite of hydrologic conditions that existed in the 20th and early 21st century. California Central Valley Groundwater‐Surface Water Simulation Model has been used previously in a variety of hypothetical outflow scenarios (Dale et al, ; Dogrul, Brush, & Kadir, ; Miller et al, ). Under a fixed level of development, water facilities, land use, water supply contracts, and regulatory requirements are held constant over the period of simulation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prior study of the watershed (MWH, ), several “level of development” scenarios using the California Central Valley Groundwater‐Surface Water Simulation Model (Brush, Dogrul, & Kadir, ) were created to simulate a suite of hydrologic conditions that existed in the 20th and early 21st century. California Central Valley Groundwater‐Surface Water Simulation Model has been used previously in a variety of hypothetical outflow scenarios (Dale et al, ; Dogrul, Brush, & Kadir, ; Miller et al, ). Under a fixed level of development, water facilities, land use, water supply contracts, and regulatory requirements are held constant over the period of simulation.…”
Section: Methodsmentioning
confidence: 99%
“…In a prior study of the watershed (MWH, 2016), several "level of development" scenarios using the California Central Valley Groundwater-Surface Water Simulation Model were created to simulate a suite of hydrologic conditions that existed in the 20th and early 21st century. has been used previously in a variety of hypothetical outflow scenarios (Dale et al, 2013;Dogrul, Brush, & Kadir, 2016;Miller et al, 2009).…”
Section: Hydrologic Modeling For 1920 Level Of Developmentmentioning
confidence: 99%
“…The continuous use of such poor quality water is causing secondary salinization and ultimately reduces crop productivity [6,51]. The groundwater quality results of Scenario I clearly indicated that an increase in the number of tube wells in the future could cause the problem of salinization; therefore, the groundwater regulation aimed at protecting the quality and quantity of groundwater resource must be implemented [61][62][63]. The predicted results of the spatial variation of groundwater salinity up to year 2030, under Scenario II, are shown in Figure 14.…”
Section: Predicted Groundwater Quality Predicted Variations Inmentioning
confidence: 99%
“…MIKE SHE; Abbott et al 1986aAbbott et al , 1986b-that simultaneously solve the governing equation of surface water (i.e., the Saint Venant equation, which describes unsteady flow on the land surface) and groundwater flow (i.e., the Richards equation, which describes unsteady flow through a variably saturated porous medium), (2) automatically coupled models, which simulate separate regions of the hydrologic and hydrogeological systems and integrate them through boundary condition links using an iterative matrix solution method (e.g., GSFLOW;Markstrom et al 2008), and (3) manually coupled models, which use separate surface and groundwater models set up independently and are calibrated to common observation data (e.g., SWAT-MODFLOW; Sophocleous and Perkins 2000;Kim et al 2008). Model selection depends on knowledge of the natural system, model functionality matching to the water resource problem being solved, available data, and computational requirements (Dogrul et al 2016).…”
Section: Introductionmentioning
confidence: 99%